The political economy of monetary policy and wage bargaining: Theory and econometric evidence - Juha Kilponen (Bank of Finland, 2000)
In this study, the determination of optimal monetary policy in unionised economies is considered from the new political economy point of view.In the empirical part of the study it is shown that, in addition to the institutional position of the central bank, labour market institutions also matter for successful anti- inflationary policy.As regards the position of the central bank, the results suggest that it is important to distinguish between the political independence of the bank and the independence of its personnel.Whereas the former helps to reduce inflation, the latter seems to produce lower unemployment and wage increases.As regards the effects of labour market institutions, the results indicate that co-ordination in wage bargaining is generally beneficial to inflation and employment, but that large differences between union density and coverage rates lead to higher wage increases and unemployment. The theoretical part of the study considers interaction between monetary policy and wage determination in unionised economies.It is shown how the benefits of delegating monetary policy to an independent, conservative central bank depend on the degree of centralisation or decentralisation in wage determination.If unions act as leaders in the "inflation game", which could happen if wage contracts are of very long duration, output in the economy remains inefficiently small.The size of this problem is the greater the more accommodative monetary policy is and the higher is the degree of centralisation in labour markets.It may be beneficial for the unions to give up their leadership position in the determination of inflation.
URN:NBN:fi:bof-201408071709
Keywords: 330; monetary policy; credibility; labour markets